Seguro agrícola no Brasil e o desenvolvimento do programa de subvenç\~ao ao prêmio - Gesmar Rosa dos Santos; Alexandre Gervásio de Sousa; Gustavo Alvarenga (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Agricultural insurance is of great importance to agriculture of a country in terms of its role for farmers rent. Moreover, the fact that the crop insurance represent only 0.4% of the amount of the insurance market in Brazil indicates a large space to grow. Such markets, including internationally, keep deep relationship of dependence on public support. In this sense, the insurance premium subvention program (PSR), a federal government initiative, has been a major incentive for insurers and farmers adhesion. This study describes the trajectory of the PSR from the point of view of the government action, focused on descriptive aspects that allow the analysis of the goals of the program. We analyze the PSR based on official data from the period 2006-2011. It was observed that this market is limited to 294 municipalities and seven states in the year 2011. Another point worth noting is that the data reflect a market size with standard incentives, but also reflects the combination of mechanisms and strategies of insurers to enhance their sales. One issue to be resolved by the government relates to uncertainty about the amounts and timing of release of insurance premium subvention. The discontinuity of the increase in subsidy, having been reduced by 23.4%, from 2009 to 2010, left consequences in both the producers and insurers. We conclude that the PSR is an essential action for the development of agricultural insurance in Brazil. Moreover, it was observed that the market has the ability to progress with its own forces, because it has a reasonable operational margin. When the data is analyzed regionally and by type of crop they highlight the low competition in the insurance offer and a large concentration of operations in a few insurers.
Keywords: Q12; Q18; Q19; 330; rural and agricultural insurance; insurance premium subvention; production risks; crops; casualty